Pengaruh Pelayanan Pasien Terhadap Omzet Penjualan Obat Danalkes Bagian Instalasi Farmasi Rumah Sakit Tk III 04.06.03 Dr. Soetarto Yogyakarta - Tisa Mukarrahmah; suliantoro suliantoro (JMMU: JURNAL MAHASISWA MANAJEMEN DAN UMUM, 2026)
Patient service has an influence on sales turnover of drugs and medical devices because of the emergence of a good sense of service will feel happy and comfortable using the services of a pharmacy or hospital so that the quality provided and the sense of service provided by the patient will affect sales turnover, especially in the installation section. pharmacy. -The purpose of writing this final report is to find out whether there is an effect of patient care on sales turnover of drugs and medical devices in the pharmacy installation section of the TK III Hospital 04.06.03 Dr. Soetarto The writing method uses a sample of 45. By using the IMB SPSS Statistics 22 tool. The results of this paper indicate that there is a significant effect between patient care on sales turnover of drugs and medical devices carried out in the t test. From the results of table 4.9 above, t count is 4.889 and t table is 1.6810, so 4.889 > 1.6810. or t count is greater than t table so that it is concluded that ho is rejected and ha is accepted. The magnitude of the effect of patient care on sales of drugs and medical equipment is 35.7%. From the results of data processing the value of R Square (coefficient of determination) is 0.357 or 35.7%. While the remaining 64.3% is influenced by other variables.